FAKTOR – FAKTOR KEBERHASILAN USAHA PADA WIRAUSAHAWAN MUDA DI KABUPATEN PANDEGLANG - Desiyani, Risma Eka; Hidayat, Syamsul; Rohman, Fathur (LP2M Universitas Bina Bangsa, 2024)
Entrepreneurship is a person's effort to create a job of their own, either opening a business or creating something new to improve the economy for themselves and for others.This study aims to determine the influence of business interest on business success in young entrepreneurs, the influence of business motivation on business success in young entrepreneurs, and self-efficacy on business success in young entrepreneurs in Pandeglang district.The research method used is quantitative. By using primary data. The total population in this study amounted to 189,660 business actors and the sample used was 100 samples of business actors in Pandeglang Regency. This research was processed using SmartPLS data test version 0.4.The results of the t-test of the Business Interest statistics on business success in young entrepreneurs show a statistical T value of 6,229 > table 1,661 with a significant level of 0,000. This means that the Business Interest variable has a significant effect on business success in young entrepreneurs. Motivation obtained a statistical T value of 0.799 < table 1.661 With a significant level of 0.424, this indicates that the variable Business Motivation does not have a significant effect on Entrepreneurship. While Self-Efficacy obtained a t-statistic value of 2,003 > table 1,661 With a significant level of 0.045, this indicates that the Self-Efficacy variable has a significant effect on business success in young entrepreneurs.The conclusion of this study is that there is an influence on business interest variables and self-efficacy variables on business success in young entrepreneurs in Pandeglang Regency. However, in the variable of business motivation, there is no influence on business success on young entrepreneurs in Pandeglang district.